1997
DOI: 10.1210/jcem.82.2.3754
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin and Growth Hormone-Releasing Hormone in Normal and Tumoral Human Breast Tissue: Endogenous Content, in Vitro Pulsatile Release, and Regulation

Abstract: Endogenous production of SRIH and GHRH was analyzed in human breast tissue. SRIH precursor (pro-SRIH) was identified after Sephadex G-50 filtration of acetic acid extracts of normal and tumoral human breast samples. SRIH-(1-14) or -(1-28) could not be detected in breast tissue, whereas the immunoreactive SRIH released in vitro was characterized as SRIH-(1-28). Endogenous production of GHRH was assessed by identification of GHRH messenger ribonucleic acid by PCR followed by sequencing of the amplified complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
0
7
0
3
Order By: Relevance
“…However, the mechanism of action of GHRH antagonists remains to be clarified. It was shown that several human cancers and cancer cell lines produce GHRH (34,35,39). GHRH-sensitive receptors on various tumor cells have been also described (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of action of GHRH antagonists remains to be clarified. It was shown that several human cancers and cancer cell lines produce GHRH (34,35,39). GHRH-sensitive receptors on various tumor cells have been also described (19).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the hypothalamus, GHRH also is produced in various peripheral tissues including tumors (34,35). The receptors for GHRH also were detected in various extrapituitary organs (36).…”
mentioning
confidence: 99%
“…However various studies indicate that GHRH, in addition to stimulating the release of growth hormone from the pituitary, functions as an autocrine͞paracrine growth factor in human breast, ovarian, and endometrial cancers and SCLC (1,8,48,49). Thus the expression of mRNA for GHRH and the presence of biologically active GHRH were observed in human breast, endometrial, and ovarian cancers (48,49). Similarly, H-69 and H-510A SCLC lines express mRNA for GHRH that apparently is translated into peptide GHRH and then secreted by the cells (8).…”
Section: Screening For Svs Of Human Ghrh-r In Various Human Normal Timentioning
confidence: 99%
“…Thus, the presence of SV 1 has been shown in MIA PaCa-2 human pancreatic cancer, in some human prostatic, renal, ovarian, breast, lung, and bone cancer lines (3,18,(23)(24)(25)(26)(27)(28)(29), as well as in primary specimens of human prostate cancer (30). Furthermore, the endogenous production of GHRH was detected in diverse human cancers such as endometrial, ovarian, breast, prostatic, pancreatic, gastric, colon cancers, SCLC, and sarcomas (21,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The proliferation of SCLC, sarcomas, and breast cancer cells can be stimulated by administration of GHRH or its agonistic analogs and conversely inhibited by GHRH antagonists.…”
Section: Iverse Antagonistic Analogs Of Growth Hormone (Gh)-mentioning
confidence: 99%